Utility of BRAF V600E Mutation-Specific Immunohistochemistry in Detecting BRAF V600E-Mutated Gastrointestinal Stromal Tumors. Issue 5 (1st November 2015) - Patil, Deepa T.; Ma, Shuang; Konishi, Mai; Carver, Paula D.; Pukay, Marina; Beadling, Carol; Corless, Christopher L.; Rubin, Brian P.
Abstract: Objectives: As patients with BRAF V600E mutation respond to BRAF inhibitors, it is important to identify these mutations to stratify patients for the appropriate therapy. In this study, we evaluated the utility of a BRAF V600E allele-specific antibody in gastrointestinal stromal tumors (GISTs). Methods: BRAF V600E mutation-specific immunohistochemistry (negative, weak, or moderate/strong expression) and BRAF sequencing were performed on 38 consecutive GISTs diagnosed between January 2013 and April 2014. Results: GISTs from a cohort of 25 men and 13 women (mean age, 61 years; range, 39–88 years) were localized to the stomach (18), small bowel (10), colon (three), rectum (two), and pelvis/omentum (five). Strong and diffuse cytoplasmic BRAF expression was noted in two (5%) of 38 cases, while eight (21%) of 38 cases showed weak staining, and 28 (74%) of 38 cases were negative. Both of the strongly positive cases arose in the stomach, occurring in a 42-year-old and a 47-year-old woman, respectively. The lesions measured 0.8 and 1 cm, showed spindle cell morphology, and had no risk of progressive disease by Miettinen criteria. Both cases showed heterozygous BRAF V600E, while no BRAF mutations were detected in cases with weak or negative BRAF expression. Conclusions: BRAF V600E mutation-specific immunohistochemistry is a highly sensitive and specific method for detecting BRAF -mutated GISTs.